KEPEMIMPINAN SITUASIONAL PENGELOLA PROGRAM KESETARAAN PAKET C DI PKBM HANG TUAH KOTA PEKANBARU - Ayulia Ayulia; Said Suhil Achmad; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the situational leadership of the organizer of the C package equality program at the Hang Tuah PKBM Pekanbaru City. This study uses a descriptive qualitative paradigm approach. The research subjects will be determined based on purposive sampling, there are 5 (five) informants in this study. Data collection is done by observation (observation), documentation, in-depth interviews (indept interviews), data analysis is done by: data reduction (data reduction); data exposure (data display); and conclusion drawing and verification (conclusion drawing / verifying). The results showed: 1) The manager of the C package equality program implements the situational leadership style, from the indicator the manager acts as an instructor / informs that it has been carried out, consulted / peddled, participated / involved delegating / delegated, 2) the factors supporting situational leadership are the manager of the C package equality program always trying to embrace all parties in carrying out their duties, being fair, providing motivation, having HR in accordance with competency standards, availability of adequate facilities and infrastructure of PKBM. While the inhibiting factors include a number of managers who have difficulty communicating with leaders, 3) Impact of situational leadership in managing the C package equality program at the Hnag Tuah PKBM Pekanbaru City, where up to now the Hnag Tuah PKBM institution has received an "B" accreditation score, and the program equality of the best C packages in Pekanbaru City.Key Words: Leadership Situational, Manager.